Emprendimiento y arreglos institucionales para el desarrollo local. Análisis de un programa de codesarrollo en Colombia (2016)
Co-development is an international cooperation strategy based on the formulation of programs seeking to manage international migration and promote local development. The city of Pereira in Colombia has undergone several programs recently co-development. This article analyzes the hispanic- colombian entrepreneurship training program for young university remittances called, Himigra. Through a qualitative research approach we intend to show how typical individualistic (and microsociological) premises of the undertaking and the failings of institutional coordination, own contexts of co-development, limiting the outcome of programs of this nature.